Lots of Love: A Collection of Children's Sayings - Nanette Newman (UK Collins, 1976)
GB***
compiled by Nanette Newman.
[33] p. : Byran Forbes Limited
Keywords: Theology: Miscellaneous (3GddGghJ(B: (3eJaQbGJs; Children -- Quotations; Theology